Analisis Hambatan Belajar Peserta Didik terhadap Pelajaran Biologi di Sekolah SMAN 1 Bahorok - Pakpahan, Enni; Artika, Dewi Nurul; Armiati, Rika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is a conscious effort to educate and teach students, so that students can develop from not knowing to knowing. Learning is said to be successful if the goals of the learning process can be achieved. Therefore, a process is needed that gives students the opportunity to interact actively, discover knowledge, and solve problems in learning. In this study uses a quantitative research method in 2 classes of SMA Negeri 1 Bahorok. The sample selection was done by drawing lots in three classes with the same major to take two classes that will be used as research samples (random classes in parallel classes). This research was conducted in class X at SMA Negeri 1 Bahorok, academic year 2022/2023. The number of samples in this study is 59 students, divided into 2 classes. This study aims to analyze the learning obstacles of students at SMA Negeri 1 Bahorok in class X IPA. The results of this study show that students' obstacles in learning Biology generally stem from the lack of peers to discuss with, so students do not have a target to aim for, which causes students to feel hopeless.